Relationship between body mass index and body condition score in Pelibuey ewes - Salazar-Cuytun, Eufracia de R.; Chay-Canul, Alfonso J.; Ptácek, Martin; García-Herrera, Ricardo A.; Rivera-Alegría, Flor de María; Aguilar-Caballero, Armando J.; Sarmiento-Franco, Luis A. (Ecosistemas y Recursos Agropecuarios, 2020)
The objectives of this study were to detect the relationship between body mass index (BMI) and body condition score (BCS) in Pelibuey ewes to predict BMI based on well-known BCS estimation. The body weight (BW), withers height, (WH), body length (BL) and BCS were determined in 402 ewes. The BMI was calculated as: BMI = (BW (kg)/WH (m)/ BL (m))/10. Relationships were estimated by means of regression models using PROC REG of the SAS. The BMI and the BCS showed a high relationship; correlation coefficient (r) of 0.80 (P
Keywords: Body mass index; body measurements; body fat; energy reserves